Isolasi dan Identifikasi Kandungan Metabolit Sekunder Jamur Endofit Rimpang Kunyit (Curcuma longa linn.) - Dewi Chusniasih; Najla Nur Azizah; Salsa Pratiwi Mulyadi; Fitri Rizki Oktariyani (Jurnal Pendidikan Biologi Undiksha, 2024)
Turmeric is a plant that is often used as an ingredient in traditional medicine. Turmeric rhizome contains secondary metabolites such as alkaloids, triterpenoids, flavonoids, tannins, anthraquinones and polyphenols which have the potential to be used as antimicrobials and antioxidants. Endophytic fungi that live in plant tissue can produce the same metabolites as their host plants, so that endophytic fungi from turmeric rhizomes have the potential to produce secondary metabolites of medicinal ingredients. This research aimed to isolate endophytic fungi from turmeric rhizomes, and identify secondary metabolites produced by these endophytic fungi. Endophytic fungal isolates were carried out using the pour plate method, and purification was carried out on each colony which had different characteristics. Identification of secondary metabolites was carried out qualitatively. The results showed that there were 5 isolates of endophytic fungi from turmeric rhizomes, namely isolates J1, J2, J3, J4, and J5. The five isolates of endophytic fungi were positive for containing alkaloids, tannins and phenolics, but only isolates J2, J3 and J4 also produced saponins. The five isolates of endophytic fungi were reported not to produce flavonoid compounds. Secondary metabolites produced by endophytic fungi from turmeric rhizomes have the potential to be used as antimicrobial and antioxidant natural ingredients.